2017
DOI: 10.1088/1751-8121/aa96f4
|View full text |Cite
|
Sign up to set email alerts
|

Solitons in a Hamiltonian $\newcommand{\PT}{\mathcal{ PT}}{\boldsymbol \PT}$ -symmetric coupler

Abstract: Abstract. We introduce a nonlinear parity-time-symmetric dispersive coupler which admits Hamiltonian and Lagrangian formulations. We show that, in spite of the gain and dissipation, the model has several conservation laws. The system also supports a variety of exact solutions. We focus on exact bright solitons and demonstrate numerically that they are dynamically stable in a wide parameter range and undergo elastic interactions, thus manifesting nearly-integrable dynamics. Physical applications of the introduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Non-Hermitian parity-time (PT ) symmetry physics has experienced rapid developments in the last two decades, especially in the field of optics, where the balanced optical gain and loss can be modeled by a PT -symmetric Hamiltonian, and it is found that gain and loss can serve as new engineering tools and also lead to abundant new and unexpected features [34][35][36][37][38]. These great developments inspired the interest in extending cold atom physics from Hermitian to non-Hermitian regime, with the prospect of exploring unidirectional transportation [39], non-Hermitian skin effect [40][41][42][43], soliton [44][45][46], double-well [47][48][49] and Hubbard model [50,51] in open environments, etc. In cold atom systems, controlled atomic loss can be realized by extracting atoms from the atomic gas via atom-light interaction [52]; while the atomic gain is proposed to be realized by injecting atoms into the atomic gas using an atom laser [53].…”
Section: Introductionmentioning
confidence: 99%
“…Non-Hermitian parity-time (PT ) symmetry physics has experienced rapid developments in the last two decades, especially in the field of optics, where the balanced optical gain and loss can be modeled by a PT -symmetric Hamiltonian, and it is found that gain and loss can serve as new engineering tools and also lead to abundant new and unexpected features [34][35][36][37][38]. These great developments inspired the interest in extending cold atom physics from Hermitian to non-Hermitian regime, with the prospect of exploring unidirectional transportation [39], non-Hermitian skin effect [40][41][42][43], soliton [44][45][46], double-well [47][48][49] and Hubbard model [50,51] in open environments, etc. In cold atom systems, controlled atomic loss can be realized by extracting atoms from the atomic gas via atom-light interaction [52]; while the atomic gain is proposed to be realized by injecting atoms into the atomic gas using an atom laser [53].…”
Section: Introductionmentioning
confidence: 99%